System design and control integration for advanced manufacturing - Li, Han-Xiong.; Lu, XinJiang (Manufacturing researcher) (Hoboken, New Jersey : John Wiley & Sons Inc., 2014)
Most existing robust design books address design for static systems, or achieve robust design from experimental data via the Taguchi method. Little work considers model information for robust design particularly for the dynamic system. This book covers robust design for both static and dynamic systems using the nominal model information or the hybrid model/data information, and also integrates design with control under a large operating region. This design can handle strong nonlinearity and more uncertainties from model and parameters.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher.
Keywords: Intelligent control systems; Computer integrated manufacturing systems; Computer integrated manufacturing systems; Intelligent control systems; TECHNOLOGY & ENGINEERING / Engineering (General); Electronic books; Electronic books